Manajemen Sekolah dalam Peningkatkan Aktivitas dan Prestasi Belajar Siswa - Ananda, Miftah Rizki (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The success of the teaching and learning process in the classroom is largely determined by the learning strategies implemented by the teacher appropriately. This research is based on the problem: How do students' learning activities increase? improving student learning outcomes,? the relationship between activities and student learning outcomes. The aim of the research is to determine the increase in learning activities, increase in learning outcomes, the relationship between activities and learning outcomes. This research uses two rounds of action research. Each round consists of four stages, namely: design, implementation, observation, and reflection. Conclusions from research using Cooperative Group Investigation are proven to increase: (a) student learning activities, (b) student learning outcomes, (c) positive and significant relationship between activities and student learning outcomes.